Neoliberalism and the violation of students’ rights: The case of English language education (Journal of Applied Learning and Teaching, 2024)
This theoretical study explores the impact of neoliberalism on education, specifically focusing on its influence in the areas of general education and English language teaching. Neoliberalism, a complex concept with varied interpretations, advocates for free markets, privatisation, and individual entrepreneurship as a means to enhance human well-being. In the context of education, neoliberal ideologies have led to the commodification of education, the transfer of educational responsibility from the government to individual households, and the emphasis on standardised testing and accountability measures. The impact of neoliberalism is particularly pronounced in the English language teaching sector, where English is viewed as a valuable economic asset and a tool for individual advancement in the market-driven economy. Despite the growing awareness of neoliberalist influences, there is a need for further academic exploration and critical inquiry to understand its pervasive effects on education systems and learners. Regarding the matter, this study discusses the influence of neoliberal ideologies on textbooks and materials, which often promote themes of employability, consumerism, and entrepreneurship.